HOW DO R&D AND FIRM SİZE PLAY A ROLE IN THE RELATIONSHIP BETWEEN PUBLIC INCENTIVES AND FIRM PERFORMANCE? (Third Sector Social Economic Review, 2022)
The aim of this study is to examine the level of benefiting from the incentives applied according to the size of the companies operating in Turkey and the reflections of these incentives on their performance. In examining the relationship between incentives and performance, the effects of firms having R&D departments and firm sizes are discussed interactively. In this context, the data obtained through questionnaires from 577 managers were evaluated with SPSS and Process Macro applications. Explanatory factor, regression and regulatory variable analyzes were performed in the study.According to the results of the study, the level of benefiting from public incentives, the existence of R&D departments and the size of the firms affect their general and financial performances negatively and significantly. This relationship becomes positive and meaningful for companies with R&D departments benefiting from incentives, large companies benefiting from incentives and large companies with R&D departments. In the detailed analyzes made in this context, as the companies get smaller, there is a significant effect in favor of those who do not have an R&D department in the effect of public incentives on the company's (general and financial) performance. Moreover, this situation has the opposite effect on those who have an R&D department. On the other hand, it has been observed that as the firm grows, the effect of public incentives on general and financial performance increases significantly in favor of firms with R&D departments. In other words, as the level of incentive increases in large firms with R&D departments, performance increases significantly, whereas in large firms without R&D department, the increase in incentives shows a negative and significant relationship with performance.
Keywords: Public Incentive; R&D; Firm Size; Firm Performance.